Effects of Deficit Irrigation on Canopy Temperature Dynamics and Physiology of Landscape Groundcovers - Anish Sapkota; Amir Haghverdi; Donald Merhaut (HortScience, 2023)
Identifying the irrigation-induced cooling effects from a particular plant species used for urban groundcovers while optimizing the rates of irrigation applications is important in regions with hot and dry summers. A 2-year (2020–21) study was conducted in Riverside, CA, USA, to evaluate the effect of irrigation rates on the canopy temperature dynamics of 10 urban groundcovers. Four reference evapotranspiration (ETo)-based irrigation treatments (20%, 40%, 60%, and 80% ETo) and 10 groundcovers were laid in a randomized complete block design and replicated three times. The effect of irrigation rates on the difference between canopy–air temperature (ΔT), leaf area index (LAI), and stomatal conductance (gs) were evaluated. All response variables were collected between May and October 2020 and 2021. The crop water stress index for five groundcovers was also computed. The ΔT was affected (P < 0.05) by irrigation rates, and groundcovers, including Rhagodia spinescens and Baccharis × ‘Starn Thompson’, maintained the canopy temperature less than the ambient air temperature for all irrigation rates imposed. For most of the groundcovers, the ΔT yielded a strong relationship with LAI (r = –0.41 to –0.73), and gs (r = –0.35 to –0.60). Crop water stress index also showed a strong correlation to normalized difference vegetation index (r = 0.42 to –0.72) and gs (r = –0.57 to –0.64). Irrigation-included cooling was evident in most groundcovers irrigated at higher rates; however, Rhagodia spinescens and Baccharis × ‘Starn Thompson’ were found to perform well in cooling ability and maintaining the canopy growth as evidenced by LAI. Our study showed that proper plant selection and irrigation management could help maintain green spaces and mitigate the urban heat island effect while conserving irrigation water.